Possibilities of Using Rivaroxaban in Elderly Patients with Atrial Fibrillation: Data from Randomized Studies and Real Clinical Practice - N. M. Vorobyeva; O. N. kacheva (Рациональная фармакотерапия в кардиологии, 2018)
The possibility of rivaroxaban using in elderly patients with non-valvular atrial fibrillation is discussed in the review. The results of ROCKET-AF randomized trial, including subgroup analysis in patients older than 75 years, are presented. The problem of unreasonable prescription of low doses of anticoagulants in real clinical practice and questions of adherence of patients to anticoagulant therapy are discussed. The results of two recent studies of actual clinical practice performed in patients over the age of 80 and 85 years, respectively, are presented as well as favorable profile of the efficacy and safety of rivaroxaban in these age groups. Rivaroxaban reduced the risk of stroke/systemic embolism by 38% and ischemic stroke by 41% with a comparable risk of major bleeding in patients older than 80 years. In another study, in patients older than 85 years in the rivaroxaban group, a 11% reduction in the risk of death from all causes, a reduction in the risk of major bleeding by 10% and an acute coronary syndrome by 14%, with similar risk of stroke/systemic embolism, clinically significant minor bleeding and a combined endpoint (stroke/systemic embolism, large bleeding, death from all causes) have been found.